Dampak Sosialisasi Penggunaan E-money Gopay terhadap Pertumbuhan UMKM di perumahan Sudirman Indah Tigaraksa - Rasyiddin, Ahmad; Eka cipta cendikia Naufal; Febri Sari Siahaan; Caesar Rismanto (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
The use of e-money such as Gopay has become a popular payment solution in various economic sectors, including micro, small and medium enterprises (MSMEs). This research aims to examine the impact of socializing the use of Gopay e-money on the growth of MSMEs in the Sudirman Indah Tigaraksa Housing Complex. This socialization is expected to increase operational efficiency and market access for MSMEs, as well as support local economic growth. The research methods used include surveys and structured interviews with MSME owners who have participated in the Gopay socialization program. The data collected was analyzed using linear regression techniques to measure the influence of socialization on MSME growth, which was measured through increased sales, operational efficiency and market access. The research results show that socialization of the use of Gopay has a positive and significant impact on the growth of MSMEs. MSMEs that use Gopay experience an increase in sales of 25% and an increase in operational efficiency of 20%. Apart from that, using Gopay also increases MSME market access by making transactions easier and expanding customer reach. This research concludes that the socialization of Gopay e-money is effective in supporting the growth of MSMEs in the Sudirman Indah Tigaraksa Housing Complex. Therefore, it is recommended that the government and related parties continue to encourage the adoption of e-money among MSMEs to increase the competitiveness and sustainability of their businesses. This journal provides recommendations for implementing a wider and more intensive e-money socialization program to support the development of MSMEs in various economic sectors.